2016
DOI: 10.1021/acs.energyfuels.6b02115
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Stability of Bagasse Biocrude from Liquefaction Stored in Real Conditions

Abstract: The stability of biocrude produced from the liquefaction of sugarcane bagasse in ethanol was observed. The degradation characteristics of biocrude and reference fuels, such as diesel, waste cooking oil biodiesel, and their blends, were studied under three different storage environments and temperatures over 24 weeks, namely, hot (43 °C), cold (4 °C), and outdoor (variable temperature) conditions. Higher Heating Values of biocrude had only small changes for all storage conditions, and this was similar to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Temperature and reaction time are the two most common parameters studied in HTL treatment while liquid to solid ratio is another parameter that affects liquefaction. In most of these studies, there is combination of different solvents such as black liquor, alkaline or ethanol (Yuan et al , ; Long et al , ; Kosinkova et al , ) with the focus towards biofuel but with our research targeted towards emulsion studies, water was the best solvent without the extra steps for neutralisation or by‐products disposal.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature and reaction time are the two most common parameters studied in HTL treatment while liquid to solid ratio is another parameter that affects liquefaction. In most of these studies, there is combination of different solvents such as black liquor, alkaline or ethanol (Yuan et al , ; Long et al , ; Kosinkova et al , ) with the focus towards biofuel but with our research targeted towards emulsion studies, water was the best solvent without the extra steps for neutralisation or by‐products disposal.…”
Section: Resultsmentioning
confidence: 99%
“…The water content of biocrude could affect the physicochemical properties of biocrude and showed a positive or negative influence based on diverse applications. A high water content would reduce the heating value and the homogeneity of biocrude and its solubility in fossil-based fuels, whereas a moderate water content might benefit the viscosity of biocrude. , Currently, the water content has been another signal index to the stability of biofuels. Hence, we evaluated the water content of the biocrude during storage.…”
Section: Resultsmentioning
confidence: 99%
“…The major difference in viscosity between pyrolysis and Density values for LC bio-oils are typically higher than 1000 kg/m 3 , with small variations depending on the source of biomass. For example, values between 970 kg/m 3 and 1100 kg/m 3 are typical for HTL biocrudes [9,45,46]. Somewhat higher values are typically reported for pyrolysis oils, namely between 1100 kg/m 3 and 1200 kg/m 3 [47].…”
Section: Processmentioning
confidence: 95%
“…Another important aspect of LC bio-oils is the stability under storage. Kosinkova et al [46] reported an increase in density of about 5% for an HTL biocrude under ambient conditions upon 25 weeks of storage. The increase reached 30% when the biocrude was stored at 43 • C for the same duration.…”
Section: Processmentioning
confidence: 99%